RESEARCH AND MATHEMATICAL MODELING OF TURBULENT BOUNDARY LAYER AT POSITIVE PRESSURE GRADIENT - Mamchuk, Vitaliy; Lastivka, Ivan; Bezverkhyi, Oleksandr (Proceedings of National Aviation University (archive), 2016)
Purpose: Mathematical modeling of complex turbulent near-wall flows, that occur during the flow of airfoils, is impossible without understanding the nature of the flow in boundary layer. From a mathematical point of view, the calculation of such flows, because in practical problems they regarded as turbulent, and the characteristics of turbulence are largely dependent on the geometry of the profile of the longitudinal component of the average velocity of the near-wall flow. Based on this, the purpose of this work is studying and mathematical modeling of turbulent near-wall flows in the interaction with the real streamlined surface, that has certain features, such as the curvature, roughness, etc., as well as the study and research of the influence of the pressure gradient on the empirical coefficients, parameters of the flow, velocity profiles and friction stress. Methods: We performed the calculations using numerical finite-difference marching method with algebraic model of turbulent viscosity coefficient. Results: In this paper we present some results of the numerical study of the effect of the positive pressure gradient on the empirical coefficients of the transition zone and the law of the near-wall and the outer-wall areas. Discussion: Comparison of the calculated results with the experimental data shows that the proposed approaches provide an opportunity to simulate the flow as close as possible to their physical properties. Presented mathematical model for the calculation of turbulent boundary layers and near-wall flows makes it possible to calculate such a complex and valuable from a practical point of view type of the flow as the aerodynamic trail behind the streamlined body.